Koolen‐de Vries syndrome in a 63‐year‐old woman: Report of the oldest patient and a review of the adult phenotype. Issue 2 (19th October 2021) - Farnè, Marianna; Bernardini, Laura; Capalbo, Anna; Cavarretta, Giusy; Torres, Barbara; Sanchini, Mariabeatrice; Fini, Sergio; Ferlini, Alessandra; Bigoni, Stefania
Abstract: Koolen‐de Vries syndrome (KdVS) is a rare genetic disorder caused by a de novo microdeletion in chromosomal region 17q21.31 encompassing KANSL1 or by a de novo intragenic pathogenic variant of KANSL1 . KdVS is typically characterized by intellectual disability (ID), variable from mild to severe, developmental psychomotor delay, especially of expressive language development, friendly disposition, and multiple systemic abnormalities. So far, most of the individuals affected by KdVS are diagnosed in infancy or in adolescence; to the best of our knowledge, only 34 (including ours) adults have been reported in literature. Here we present the adult phenotype of a 63‐year‐old Italian woman affected by KdVS, caused by a 17q21.31 microdeletion. She is, to our knowledge, the oldest affected individual reported so far. We collected her clinical history and photographs, as well as those of other 26 adult patients described so far and compared her to them. We propose that the cardinal features of KdVS in adulthood are ID (ranging from mild to severe, usually moderate), friendly behavior, musculoskeletal abnormalities (especially scoliosis), and facial dysmorphism (a long face and a pronounced pear‐shape nose with bulbous overhanging nasal tip). Therefore, we suggest considering KdVS in differential diagnosis in adult patients characterized by these features.